A review of perovskite solar cell (PSC) : Its revolution and mathematical modelling - Yao, Lee Jin; Rahifa, Ranom; Kyairul Azmi, Baharin; Norhafizah, Md Sarif (Asian Research Publishing Network, 2023)
Perovskite solar cell (PSC) is one of the third-generation type of solar cells that has high efficiency and can be produced at a lower cost compared to silicon-based solar cells. However, one of its core problems is the uncertainty of its short-and long-term stability. To minimise this risk, proper modelling is required to assess its potential performance before fabrication. Modelling of PSC is also important to prevent wastage of time and optimise material use. This work provides a comprehensive review of current PSC circuitry and the electrochemical modelling techniques available. Circuitry modelling relates to the operation conditions where PSC is represented by an equivalent circuit model that contains a resistor, diode, photo-generated current source, and others. Meanwhile, electrochemical modelling refers to the operation mechanism of PSC and can be represented by mathematical equations that include parameters of charge density of the layers, drift, diffusion, generation, and recombination process of charge carriers. This paper also summarizes the numerical algorithms and modelling simulations used such as SCAPS, AFORS-HET, COMSOL Multiphysics, MATLAB to evaluate PSC model performance. Through this paper, a summary of the modelling results has been compiled covering various aspects of fabrication including the material’s layer thickness, doping concentration, electron affinities as well as temperature distribution within the PSC during operation.